THE EFFECT SNPs R25C AND R25H LEPTIN GENE TO CHOLESTEROL AND TRIGLYCERIDE ON BLOOD OF ONGOLE CROSSBREED CATTLE - Hilmia, Nena; Dudi, Dudi; Edianingsih, Primiani; Mushawir, Andi; Susilawati, Iin; Pangestu, Muhammad Syahid Panji; Widyastuti, Rini (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
Single Nucleotide Polymorphisms (SNPs) on the Leptin gene may alter the quality and quantity of Leptin hormone, which plays an active role in energy metabolism and it can contribute to fat deposition in mammals. This study proposed to determine the effect of SNPs R25C and R25H on Cholesterol, and Triglycerides levels in the blood of Ongole Crossbreed cattle. The research was carried out experimentally with a Completely Randomized Design using the sixteen heads of Ongole Crossbreed. There were three different genotypes based on SNPs R25C and R25H: CC, TT, and  AA. The cattle were reared intensively for two months. The feed consists of corn kernels and concentrates, and It is calculated based on the Dry Matter (DM) intake, which is 3% of body weight. The result showed SNPs R25C and R25H on the Leptin gene did not have a significant effect on blood Cholesterol, and Triglyceride levels of Ongole Crossbreed cattle. Those SNPs in the Leptin gene cannot be used as selection markers in Ongole Crossbreed cattle. Further research is needed to include SNPs in other genes contributing to Cholesterol and Triglycerides on blood cattle